Intrinsic multiscale structure and dynamics in complex electronic oxides : (World Scientific, 2003)
There is considerable interest in the intrinsically multiscale structure and dynamics of complex electronic oxides, especially since these materials include those of technological importance, such as colossal magnetoresistance manganites and cuprate high temperature superconductors. Current microscopies, such as diffuse X-ray and inelastic neutron scattering, electromagnetic and acoustic response, NMR and scanning tunneling microscope probes, have revealed static and dynamic multiscale patterns in charge positioning, lattice structure and magnetic orientation, that respond to both external stress and magnetic field. These self-organized patterns include charge and orbital ordering; stripes in strain/spin; and labyrinth-like conductance modulations. The materials exhibit nanoscale phase segregation and mesoscale inhomogeneous clustering, and their phase transitions can have a percolative character.